2019
DOI: 10.3390/en13010082
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Scorecard-Based Evaluation of Sustainable Energy Investment Projects with IT2 Fuzzy Hybrid Decision Making Approach

Abstract: The purpose of this study is to determine the issues that financial institutions should pay attention to in their decision to provide financing to large scale energy projects. Within this framework, taking into account the Balanced Scorecard (BSC) approach, 4 dimensions and 8 criteria that can be effective in these decisions of financial institutions were determined. After that, the importance weights of these dimensions and criteria were determined by interval type-2 (IT2) fuzzy DEMATEL method. In addition, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 90 publications
(103 reference statements)
0
24
0
Order By: Relevance
“…Applying a SWOT analysis, the study suggested that Fintech applications have a significant influence on the credit system. Additionally, Zhou et al (2018) provided supporting evidence for the positive impact of Fintech applications on the effectiveness of credit card systems. Sun (2018) and Chang et al (2017) also underlined the importance of Fintech investments in the performance of such systems was also underlined.…”
Section: Literature On Fintechmentioning
confidence: 83%
See 1 more Smart Citation
“…Applying a SWOT analysis, the study suggested that Fintech applications have a significant influence on the credit system. Additionally, Zhou et al (2018) provided supporting evidence for the positive impact of Fintech applications on the effectiveness of credit card systems. Sun (2018) and Chang et al (2017) also underlined the importance of Fintech investments in the performance of such systems was also underlined.…”
Section: Literature On Fintechmentioning
confidence: 83%
“…Details of this process are revealed in Eq. (1) (Soto et al 2019;Zhou et al 2020). Budgeting (alternative 4) Kazan et al (2018) and Gozman et al (2018) Borrowings (alternative 5) Chen ( 2018), Liu et al (2015) and Kauffman et al (2015) Table 3 The details decision makers (DM) Within this context, µÃ(x, u) can take values between 0 and 1.…”
Section: Interval Type-2 Fuzzy Setsmentioning
confidence: 99%
“…In lots of different studies in which fuzzy multi-criteria decision-making methods are considered, three different experts made evaluations [65][66][67][68]. This situation is quite similar in most of the studies related to energy investment [69][70][71][72]. Hence, it is thought that the evaluations of three experts are quite enough in such an analysis.…”
Section: Discussionmentioning
confidence: 86%
“…Pandey et al [34] also made a similar analysis for different country groups. Additionally, Zhou et al [35] tried to find the issues that finance companies should consider in order to finance large-scale energy investments. Dinçer and Yüksel [36] used the IT2 fuzzy DEMATEL approach to find the key strategies for tourism investments to be innovative.…”
Section: Literature Review On Methodologymentioning
confidence: 99%